Elemental analyses and determination of lead content in kohl (stone) by laser-induced breakdown spectroscopy - Haider, Abul Fazal Mohammed Yusuf; Lubna, Rebeka Sultana; Abedin, Kazi Monowar (© 2012 Society for Applied Spectroscopy, 2017)
This article was published in the Journal Applied Spectroscopy [© 2012 Society for Applied Spectroscopy] and the definite version is available at : http://journals.sagepub.com/doi/abs/10.1366/11-06407